Genetic characterization of porcine reproductive and respiratory syndrome virus from Eastern China during 2017–2022 - Zhou, Lujia; Yang, Yang; Xia, Qiqi; Guan, Zhixin; Zhang, Junjie; Li, Beibei; Qiu, Yafeng; Liu, Ke; Shao, Donghua; Ma, Zhiyong; Wang, Xiaodu; Wei, Jianchao (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is an immunosuppressive disease caused by PRSS virus (PRRSV). PRRSV mainly causes reproductive disorders in pregnant sows and respiratory diseases in piglets. Recently, it has emerged as one of the most important diseases of the pig industry across the globe. In this study, we have collected 231 samples from differently sized pig farms in Eastern China from 2017 to 2022 to investigate the epidemic characteristics of the disease. All samples were screened by RT-PCR and analyzed further using Nsp2 and ORF5 genes. The result showed that the positive rate of PRRSV was 24% (54/231). Phylogenetic analysis (13 positive samples) revealed that all isolates belonged to genotype 2, and they were mainly distributed in four lineages (i.e., lineage 1, 3, 5, and 8). Nsp2 is the most variable protein among all PRRSV NSPs, several isolates from this study had amino acid deletions within Nsp2 compared to that of strain VR-2332. The major structural protein glycoprotein (GP5) protein is encoded by ORF5. Epitope analysis of the 13 isolated strains and additional reference strains revealed that all 13 strains had some mutations on the decoy epitope, the primary neutralizing epitope, T cell epitopes, and B cell epitopes. This study showed that the prevalent PRRSV strain in Eastern China was still HP-PRRSV, while the proportion of NADC30-like and NADC34-like strains have increased. This study further enriches the epidemiological data of PRRS in Eastern China and provides a theoretical basis for vaccine development and prevention and control of the disease across the region.